The Diploma-Coaches-Study at the Coaches Academy Cologne of the German Olympic Sport Federation - Nordmann, L.; Sandner, H. (International Journal of Coaching Science, 2009)
The article presents the Diploma-coaches-study conducted by the Coaches Academy Cologne of the German Olympic Sport Federation. The study aims to achieve the specific qualification requests of national and regional sport governing committees. The study also trains selected coaches holding the highest coaching license of their association. Furthermore, it indicates that coaches are highly trained in order to acquire the highest coaching license in German elite sport or Diploma Coach in short span of time.